1987
DOI: 10.1002/jor.1100050211
|View full text |Cite
|
Sign up to set email alerts
|

Local compression patterns beneath pneumatic tourniquets applied to arms and thighs of human cadavera

Abstract: Distributions of tissue fluid pressure were examined beneath a standard pneumatic tourniquet in six upper extremities and six lower extremities of fresh human cadavera, disarticulated at the shoulder and hip, respectively. A standard 8-cm-wide tourniquet cuff was applied at mid-humerus or mid-femur position. Tissue fluid pressures were measured by 100-cm-long slit catheters inserted parallel to the bone at four tissue depths: subcutaneous, subfascial, mid-muscle, and adjacent to bone. All arms and thighs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…With or without the external pressure, the index fingertip temperatures observed for the females (27.4 75.0 1C without pressure/ 25.274.4 1C with pressure) were lower than those for the males (31.874.5 1C without pressure/29.8 74.5 1C with pressure), as depicted in the figure. Several researchers (Kirkendall et al, 1967;Hargens et al, 1987) have reported that under the same external pressure, the main arteries in a smaller arm circumference were more susceptible to deformation: a gender difference was thus implied. It seems to be the case in our study as well.…”
Section: Resultsmentioning
confidence: 97%
“…With or without the external pressure, the index fingertip temperatures observed for the females (27.4 75.0 1C without pressure/ 25.274.4 1C with pressure) were lower than those for the males (31.874.5 1C without pressure/29.8 74.5 1C with pressure), as depicted in the figure. Several researchers (Kirkendall et al, 1967;Hargens et al, 1987) have reported that under the same external pressure, the main arteries in a smaller arm circumference were more susceptible to deformation: a gender difference was thus implied. It seems to be the case in our study as well.…”
Section: Resultsmentioning
confidence: 97%
“…The cuff method used by Meendering et al (34,35) and Monahan and Ray (39) equals cuff pressure with venous pressure, assuming a 100% transmission of applied pressure to the underlying tissue. This is by no means certain, and transmission especially to the deep underlying tissue in the thigh may be overestimated (18). Further, thigh volume might differ between sexes, which could affect the found differences in calf venous compliance at transmural pressures relevant to HUT or quiet standing.…”
Section: Discussionmentioning
confidence: 98%
“…Transmission of cuff pressures to deeper tissues was significantly less in the 40-52-cm girth thighs than in the 22-33-cm girth arms. At the four tissue depths studied, tissue fluid pressures fell steeply in a longitudinal direction near the cuff edge to levels near 0 at a point 1-2 cm outside each cuff edge (14). In another study (2), longitudinal and radial tissue fluid pressure distributions were determined beneath and adjacent to wide (12 and 19 cm) pneumatic tourniquet cuffs placed on intact human cadaveric arms and legs.…”
Section: Development Of Better Tourniquet Design More Effective Comprmentioning
confidence: 99%
“…Most previous studies of tourniquet injury have focused upon the effects of ischemia in tissues distal to the applied cuff. Importantly, however, recent studies of the effects of tissue pressures on muscles, nerves, and blood vessels directly beneath the tourniquet cuff suggest that these underlying tissues are more seriously jeopardized (14,28,38,44).…”
Section: Development Of Better Tourniquet Design More Effective Comprmentioning
confidence: 99%